Proceedings of the 37th Annual Meeting of the Association for Computational Linguistics on Computational Linguistics - 1999
DOI: 10.3115/1034678.1034733
|View full text |Cite
|
Sign up to set email alerts
|

Syntagmatic and paradigmatic representations of term variation

Abstract: A two-tier model for the description of morphological, syntactic and semantic variations of multi-word terms is presented. It is applied to term normalization of French and English corpora in the medical and agricultural domains. Five different sources of morphological and semantic knowledge are exploited (MULTEXT, CELEX, AGROVOC, Word-Netl.6, and Microsoft Word97 thesaurus).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
6

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 5 publications
0
42
0
6
Order By: Relevance
“…In any case, they do not "change" the meaning as they refer to the same concept. Daille et al (1996) and Jacquemin (1999Jacquemin ( , 2001 further identified types of variation that modified the meaning of terms.…”
Section: Introductionmentioning
confidence: 99%
“…In any case, they do not "change" the meaning as they refer to the same concept. Daille et al (1996) and Jacquemin (1999Jacquemin ( , 2001 further identified types of variation that modified the meaning of terms.…”
Section: Introductionmentioning
confidence: 99%
“…Even so, real improvements are usually obtained only for incomplete and relatively short queries (Voorhees, 1994). One possibility consists in working with phrase-level semantic variation (Jacquemin, 1999), which reduces the problem of word-sense ambiguity because of the existence of a context in the complex term itself. Moreover, it would be possible to employ a fuzzy notion of synonymy which measures the degree of synonymy between two terms (Sobrino et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This set of documents is then processed by a third module, made of FASTR (Jacquemin, 1999), a shallow transformational natural language analyser and of a ranker. This module can select, among documents found by the search engine, a subset that satisfies more refined criteria.…”
Section: Selection Of Relevant Documentsmentioning
confidence: 99%
“…The original terms are extracted from the questions. The tool used for extracting text sequences that correspond to occurrences or variants of these terms is FASTR (Jacquemin, 1999). The ranking of the documents relies on a weighted combination of the terms and variants extracted from the documents.…”
Section: Document Ranking Evaluationmentioning
confidence: 99%